Rtsa gsum chos skyoṅ daṅ bcas pa la gtor ʼbul gyi rim pa khyer bde Rig ʼdzin dgaʼ ston ses bya ba bźugs so - Koṅ-sprul Blo-gros-mthaʼ-yas, 1813-1899 (s.n., 1971)
Liturgical text for the offering of the gtor-ma to the host of deities of Lamaism according to the Nyingmapa tradition.